Effects of probiotics on lipid metabolism, oxidation, and inflammation in coronary heart disease: a systematic review and meta-analysis - Yang, Xinyu; Yu, Yunfeng; Huang, Xiangning; Huang, Juan; Xiang, Qin; Yu, Rong (Frontiers in Nutrition, 2026)
ObjectiveThis meta-analysis and trial sequential analysis (TSA) aimed to evaluate the effects of probiotics on lipid metabolism, oxidative stress, and inflammation in patients with coronary heart disease (CHD).MethodsSix databases were systematically searched for relevant studies published before May 1, 2025. Basic study characteristics, outcome data, and risk of bias were extracted. Meta-analyses were performed using RevMan 5.3, TSA was conducted using TSA 0.9.5.10 beta, and publication bias was assessed using Egger’s test.ResultsEight randomized controlled trials involving 296 patients were included. Compared with the placebo, probiotics significantly reduced the low-density lipoprotein cholesterol (LDL-C) [mean difference (MD) −11.07 mg/dL, 95% confidence interval (CI) −19.94 to −2.20], malondialdehyde [standardized mean difference (SMD) −0.57, 95% CI −1.01 to −0.13], high-sensitivity C-reactive protein (MD −0.81 ng/mL, 95% CI −1.31 to −0.30), Toll-like receptor 4 (MD −4.13 ng/mL, 95% CI −5.39 to −2.88), and interleukin-6 (MD −3.22 ng/mL, 95% CI −4.01 to −2.44). Meanwhile, they increased the high-density lipoprotein cholesterol (HDL-C) (MD 2.79 mg/dL, 95% CI 0.95 to 4.63), glutathione (MD 104.66 μmol/L, 95% CI 53.74 to 155.58), and total antioxidant capacity (MD 69.51 mmol/L, 95% CI 44.64 to 94.38). However, the effects on LDL-C and HDL-C were not robust in sensitivity analyses, and neither outcome reached the minimal clinically important difference, indicating that lipid modulation is not clinically meaningful. Additionally, no significant differences were observed in very low-density lipoprotein cholesterol, total cholesterol, triglycerides, tumor necrosis factor-alpha and adverse event rate. TSA confirmed the robustness of all significant outcomes except for malondialdehyde, and Egger’s tests revealed no significant publication bias.ConclusionProbiotics exert moderate anti-inflammatory and antioxidative effects, supporting their potential as an complementary strategy for CHD. In contrast, their influence on lipid metabolism appears uncertain and clinically negligible. Given the limited certainty of evidence and the geographic concentration of available trials, high-quality multicenter studies are required to confirm these findings.